Визначення потенціалу енергозбереження процесу дистиляції сирого бензолу - Товажнянський, Леонід Леонідович; Капустенко, Петро Олексійович; Ульєв, Леонід Михайлович; Болдирєв, Станіслав Олександрович; Васильєв, Михайло Анатолійович (НТУ "ХПІ", 2010)
Present work is dedicated to studying of the benzene distillation process and energy saving retrofit of existing flowsheet by process integration methods. Target values of cold and hot utilities of existing process were determined. Hot and cold utilities consumption was reduced on 35 % and 12.3 % respectively. It was achieved by ΔТmin decreasing and cross pinch blocking. Design of the optimal heat exchangers network design was outlined
Keywords: економія енергії; коксовий газ; масляний дефлегматор; пінч-аналіз